Juridical Analysis of Regulations Controlling Import or Export of Goods That are Suspected of Originating from Intellectual Property Infringement, Particularly on Registered Trademarks - Liah Anggraeni Basuki (Yuridika, 2021)
Protection of intellectual property laws can start from the action of preventing the entry or exit of goods from a country. The Directorate General of Customs and Excise, Ministry of Finance of the Republic of Indonesia, which is the implementing agency in the customs sector, can control the import or export of goods suspected of being or originating from the result of intellectual property infringement. This is a financial activity involving several institutions, including the Directorate General of Customs and Excise, the Ministry of Finance of the Republic of Indonesia as executor, the Directorate of Trademarks, the Ministry of Law and Human Rights as the institution that issues trademark rights, and the Commercial District Court to exercise judicial authority. Since its implementation, regulations have been made regarding the processes and conditions for controlling the export and import of goods, which accommodate the interests of the state as a regulator with the aim of regulating and harmonizing customs regulations and trademark law and the interests of rights holders or mark owners as the injured party if there is an infringement. However, there are arrangements that are ‘considered' to be detrimental to the right holder or registered mark owner in relation to the domicile of the party applying for trademark protection in the customs area. This research was conducted using a normative research type with statue and conceptual approaches. With this research, brand owners and rights holders can determine the right steps to protect their registered marks in accordance with applicable regulations.